Lifetime Costs of Prophylactic Mastectomies and Reconstruction versus Surveillance. Issue 6 (December 2015) - Mattos, David; Gfrerer, Lisa; Reish, Richard G.; Hughes, Kevin S.; Cetrulo, Curtis; Colwell, Amy S.; Winograd, Jonathan M.; Yaremchuk, Michael J.; Austen, William G.; Liao, Eric C.
Abstract : Background: The past decade has seen an increasing prevalence of prophylactic mastectomy with decreasing ages of patients treated for breast cancer. Data are limited on the fiscal impacts of contralateral prophylactic mastectomy trends, and no study has compared bilateral prophylactic mastectomy with reconstruction to surveillance in high-risk patients. Methods: Lifetime third-party payer costs over 30 years were estimated with 2013 Medicare reimbursement rates. Costs were estimated for patients choosing contralateral or bilateral prophylactic mastectomy versus surveillance, with immediate reconstructions using a single-stage implant, tissue expander, or perforator-based free flap approach. Published cancer incidence rates predicted the percentage of surveillance patients that would require mastectomies. Sensitivity analyses were conducted that varied cost growth, discount rate, cancer incidence rate, and other variables. Lifetime costs and present values (3 percent discount rate) were estimated. Results: Lifetime prophylactic mastectomy costs were lower than surveillance costs, $1292 to $1993 lower for contralateral prophylactic mastectomy and $15, 668 to $21, 342 lower for bilateral prophylactic mastectomy, depending on the reconstruction. Present value estimates were slightly higher for contralateral prophylactic mastectomy over contralateral surveillance but still cost saving for bilateral prophylactic mastectomy compared with bilateral surveillance. Present value estimates are also cost saving for contralateral prophylactic mastectomy when the modeled contralateral breast cancer incidence rate is increased to at least 0.6 percent per year. Conclusions: These findings are consistent with contralateral and bilateral prophylactic mastectomy being cost saving in many scenarios, regardless of the reconstructive option chosen. They suggest that physicians and patients should continue to receive flexibility in deciding how best to proceed clinically in each case.